A Qualitative Exploratory Study of Family Inclusion in Assertive Community Treatment: Challenges and Possibilities. Issue 2 (June 2023) - Peterson, Lance T.; Gricus, Michelle
The purpose of this study is to understand the unique challenges of Assertive Community Treatment (ACT) service providers to actively include natural supports in treatment. The qualitative approach was guided by the participatory intervention model and tenets of critical realism. Interviews included focus groups of different stakeholders on ACT teams (e.g., case managers) and individual interviews with ACT clients. Through thematic analysis, we identified themes demonstrating how state funding requirements, demands on staff schedules, and psychosocial barriers make it challenging to include clients' natural supports. We derived two implications which may enhance future possibilities for natural support inclusion: community-based psychoeducation family groups coupled with state funding streams that better support the ACT model.